2017
DOI: 10.1128/mbio.02073-17
|View full text |Cite
|
Sign up to set email alerts
|

SLC6A14 Is a Genetic Modifier of Cystic Fibrosis That Regulates Pseudomonas aeruginosa Attachment to Human Bronchial Epithelial Cells

Abstract: Cystic fibrosis (CF) is caused by mutations in the CFTR gene and is associated with progressive and ultimately fatal infectious lung disease. There can be considerable variability in disease severity among individuals with the same CFTR mutations, and recent genome-wide association studies have identified secondary genetic factors that contribute to this. One of these modifier genes is SLC6A14, which encodes an amino acid transporter. Importantly, variants of this gene have been associated with age at first ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 45 publications
3
49
1
1
Order By: Relevance
“…Indeed, it has been recently suggested that ATB 0,+ typically localizes in places where the body interfaces with microbes, such as lung and colon, where it is probably involved in reducing available nutrients to bacteria; consistently, the transporter is up-regulated in inflammatory states, such as ulcerative colitis, Crohn's disease and colon cancer [20]. Moreover, genome-wide association studies has recently identified SLC6A14/ATB 0,+ as a genetic modifier of lung disease severity in cystic fibrosis, providing a mechanism by which it regulates Pseudomonas aeruginosa attachment to human bronchial epithelial cells [40]. In that study, Di Paola et al demonstrated an enhancement of SLC6A14 expression by LPS in Calu-3 cells cultured on plasticware.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been recently suggested that ATB 0,+ typically localizes in places where the body interfaces with microbes, such as lung and colon, where it is probably involved in reducing available nutrients to bacteria; consistently, the transporter is up-regulated in inflammatory states, such as ulcerative colitis, Crohn's disease and colon cancer [20]. Moreover, genome-wide association studies has recently identified SLC6A14/ATB 0,+ as a genetic modifier of lung disease severity in cystic fibrosis, providing a mechanism by which it regulates Pseudomonas aeruginosa attachment to human bronchial epithelial cells [40]. In that study, Di Paola et al demonstrated an enhancement of SLC6A14 expression by LPS in Calu-3 cells cultured on plasticware.…”
Section: Discussionmentioning
confidence: 99%
“…SLC6A14 is an apical amino acid transporter, and we have shown that it functions to remove nutrient amino acids from the surface of respiratory epithelial cells (Di Paola et al, 2017). This function is associated with reduced adherence of Pseudomonas aeruginosa to the surface of respiratory epithelial cells (Di Paola et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, the transporter is upregulated in inflammatory states, such as ulcerative colitis, Crohn's disease and colon cancer [14]. Moreover, genome-wide association studies has been recently identified ATB 0,+ (SLC6A14) as a genetic modifier of lung disease severity in cystic fibrosis, providing a mechanism by which it regulates Pseudomonas aeruginosa attachment to human bronchial epithelial cells [24]. Compared to Calu-3 monolayers, a close similarity between the two cell models is observed only when Calu-3 layers are maintained at ALI for 8 days.…”
Section: Discussionmentioning
confidence: 99%